The fermentative activity and morphological specialitys of yeast Saccharomyces cerevisiae Y-503 at cultivation in aerobic and anaerobic conditions - S. Ts. Kotenko; E. A. Islammagomedova; E. A. Halilova (Юг России: экология, развитие, 2015)
The influence of aerobic and anaerobic conditions of cultivation on structure of cells and enzymes` activity of yeast S. cerevisiae Y-503 is researched. The results of experiment have shown that nutrient medium containing geothermal water in aerobic conditions of cultivation improves biotechnological properties of yeast important for manufacturing bread, and anaerobic activates the enzymes participating in synthesis of ethanol. Strain S. cerevisiae Y-503 can successfully be used both in baking, and in the spirit industries